Low-dose aspirin and burr-hole drainage of chronic subdural hematoma: study protocol for a randomized controlled study - Maria Kamenova; Christian Mueller; Michael Coslovsky; Raphael Guzman; Luigi Mariani; Jehuda Soleman (Trials, 2019)
Abstract Background Low-dose acetylsalicylic acid (ASA) in patients with chronic subdural hematoma (cSDH) represents a significant neurosurgical challenge. While continuation of ASA during the perioperative phase might increase recurrence and bleeding rates, discontinuation increases the risk of thromboembolic events. The aim of this study is to compare the postoperative recurrence and cardiovascular complication rates of patients undergoing burr-hole trepanation for cSDH with and without discontinuation of ASA. Methods In this prospective randomized, placebo-controlled, double-blinded study we include all patients undergoing burr-hole drainage of cSDH who are under ASA treatment. The patients are randomized into two groups, one receiving ASA and the other placebo perioperatively. The study primarily seeks to compare the rate of recurrent events under ASA to that under placebo treatment. Secondary objectives are thromboembolic event rate, perioperative blood loss, postoperative anemia, intra- and postoperative blood transfusion rate, and clinical outcome. Discussion To date, there is no evidence-based consensus on how to manage patients undergoing burr-hole drainage for cSDH who are under ASA treatment. Therefore, the decision to maintain or interrupt ASA treatment is based mostly on the surgeons’ preference. A randomized placebo-controlled study for this frequent question is urgently needed in order to provide class I evidence for the best possible treatment of this large group of patients. Trial registration ClinicalTrials.gov: NCT03120182. Initial Release: 19.04.2017. Study protocol: V2_23.02.2017